Apple Cultivation Recent Advances - Küden, Ayzin (IntechOpen, 2023)
Apple Cultivation - Recent Advances provides a comprehensive overview of recent developments in the field of pomology. It is organized into three sections: "Apple Germplasm, Molecular Characterization and In Vitro Culture", "Hormonal Regulation, Phytopathogens and Phenolics", and "Cultivars, Rootstocks, Nursery and Production Techniques of Malus Species". The book presents the latest research efforts in pomology by international authors and will open new possible research paths for further novel developments.